Mathematics Research in Association of Southeast Asian Nations Countries: A Scientometric Analysis of Patterns and Impacts - Ho-Le, Thao P.; Nguyen, Tuan V. (Frontiers in Research Metrics and Analytics, 2018)
In this study, we aimed at mapping the trend and impact of mathematics research originated from ASEAN countries by using a scientometric approach. We extracted the Web of Science's article-level data of all publications concerning mathematics research during the period of 2006-2015 for ASEAN countries. The impact of research was assessed in terms of citation, and the pattern of international collaboration was mapped by the presence of co-authorship and international affiliations. During the coverage period, ASEAN countries had published 9890 papers in mathematics, accounting for 3.8% of total ISI-indexed publications from the region. Almost 95% of the mathematics publication was from Singapore (4107 papers), Vietnam (2046), Malaysia (1927), and Thailand (1317). Approximately 54% of mathematics papers from ASEAN countries had international co-authorship, and these papers had greater citation rate than those without international collaboration. With the exception of Singapore, the citation rate for other ASEAN countries was below the world average by 8-30%. The most important predictor of citations was journal impact factor, which accounted for 5.2% of total variation in citations between papers. These findings suggest that the contribution of ASEAN countries as a group to mathematics research worldwide is modest in terms of research output and impact.